Gamma radiosensitivity study on chili (Capsicum annuum) - Omar, Shairul Rizdiyandi; Ahmed, Osumanu Haruna; Saamin, Shaharudin; Nik Ab. Majid, Nik Muhamad (Science Publications, 2008)
Induced mutation by gamma irradiation has been found to be a very useful technique for crop improvement. Apart from this, the proper use of induced mutation in plant breeding has become a profitable approach. This investigation was carried out to determine the LD50 and effect of gamma rays on germination, plant height, survival percentage, root length, root dry weight and shoot dry weight of seedlings derived from irradiated seeds of chili (Capsicum annuum). Seeds of chili were treated with 300, 400, 500, 600 and 800 Gy gamma rays at Malaysian Institute of Nuclear Technology (MINT). The treated seeds including control were sown in sand beds in size 4.6x0.7 m2 in a greenhouse at Horticulture Unit, UPMKB. Water was applied manually to maintain the soil moisture at field capacity as well as weed was manually controlled. The experiment was designed as 5x6 factorial in completely randomized design (CRD) with three replications. Lethal dose 50% of population (LD50) was assayed. Observation showed that germination percentage, plant height, survival percentage, root length, root weight and shoot dry weight decreased with increasing dose of gamma rays. The 800 Gy gamma ray dose had a profound effect on these variables perhaps due to injury the higher doses may have caused to the seeds of chili. This resulted in poor growth and development of chili seedlings. The LD50 for chili (survival percentage) was estimated at 445 Gy. Loan contracts performance determines the profitability and stability of the financial institutions and screening the loan applications is a key process in minimizing credit risk. Before making any credit In general, higher gamma ray doses particularly 600 and 800 Gy had negative effect on the morphological characteristics of chili seedlings derived from irradiated seeds.